S-PLUS: exploring wide field properties of multiple populations in galactic globular clusters at different metallicities. Issue 3 (24th May 2022) - Hartmann, Eduardo A; Bonatto, Charles J; Chies-Santos, Ana L; Alonso-García, Javier; Bastian, Nate; Overzier, Roderik; Schoenell, William; Coelho, Paula R T; Branco, Vinicius; Kanaan, Antonio; Mendes de Oliveira, Claudia; Ribeiro, Tiago
ABSTRACT: Multiple stellar populations (MSPs) are a ubiquitous phenomenon in Galactic globular clusters (GCs). By probing different spectral ranges affected by different absorption lines using the multiband photometric survey S-PLUS, we study four GCs – NGC 104, NGC 288, NGC 3201, and NGC 7089 – that span a wide range of metallicities. With the combination of broad and narrow-band photometry in 12 different filters from 3485A (u) to 9114A (z), we identified MSPs along the rectified red-giant branch in colour–magnitude diagrams and separated them using a K-means clustering algorithm. Additionally, we take advantage of the large Field of View of the S-PLUS detector to investigate radial trends in our sample. We report on six colour combinations that can be used to successfully identify two stellar populations in all studied clusters and show that they can be characterized as Na-rich and Na-poor. For both NGC 288 and NGC 7089, their radial profiles show a clear concentration of 2P population. This directly supports the formation theories that propose an enrichment of the intra-cluster medium and subsequent star formation in the more dense central regions. However, in the case of NGC 3201, the trend is reversed. The 1P is more centrally concentrated, in direct contradiction with previous literature studies. NGC 104 shows a well-mixed population. We also constructed radial profiles up to 1 half-light radius of the clusters with HST data to highlight that radial differences are lost in the inner regions of the GCs and that wide-field studies are essential when studying this.